Emerging Roles of JmjC Domain-Containing Proteins - Accari, Sandra L; Fisher, Paul R (International review of cell and molecular biology, 2015)
Jumonji C (JmjC) domain-containing proteins are a diverse superfamily of proteins containing a characteristic, evolutionarily conserved β-barrel structure that normally contains binding sites for Fe(II) and α-ketoglutarate. In the best studied JmjC-domain proteins, the JmjC barrel has a histone demethylase catalytic activity. Histones are evolutionarily conserved proteins intimately involved in the packaging of DNA within the nucleus of eukaryotic organisms. The N-termini ("tails") of the histone proteins are subject to a diverse array of posttranslational modifications including methylation. Unlike many of the other histone modifications which are transient, methylation was thought to be permanent, until the relatively recent identification of the first demethylases. Jumonji C domain-containing proteins were first identified with a role in the modulation of histone methylation marks. This family of proteins is broken up into seven distinct subgroups based on domain architecture and their ability to antagonize specific histone methylation marks. Their biological functions derive from their ability to regulate gene expression and include roles in cell differentiation, growth, proliferation, and stress responses. However, one subgroup remains, the largest, in which the JmjC domain has no known biochemical function. These proteins belong to the JmjC-domain-only subgroup and as their name suggests, the only bioinformatically recognizable domain they contain is the highly conserved JmjC domain.